2009
DOI: 10.1038/nbt.1541
|View full text |Cite
|
Sign up to set email alerts
|

Efficient siRNA delivery into primary cells by a peptide transduction domain–dsRNA binding domain fusion protein

Abstract: SUMMARYShort interfering RNA (siRNA) induced RNA interference (RNAi) responses allow for discovery research and performing large scale screening1-5; however, due to their size and anionic charge, siRNAs have no bioavailability to enter cells4,5. Current approaches fail to deliver siRNAs into a high percentage of primary cells in a non-cytotoxic fashion. Here we report an efficient siRNA delivery approach that utilizes a Peptide Transduction Domain-dsRNA Binding Domain (PTD-DRBD) fusion protein. DRBDs bind to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
279
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 319 publications
(281 citation statements)
references
References 21 publications
1
279
0
1
Order By: Relevance
“…Polyarginine (11R)-conjugated VIVIT peptide, which is a specific NFAT inhibitory peptide, was able to inhibit graft rejection of allogeneic islet transplantation in mice (Noguchi et al, 2004). More recently, TAT-CPP-conjugated RNA binding successfully delivered siRNA for efficient gene silencing in various cell types including primary T cells (Eguchi et al, 2009). Although extensive studies have suggested the possible use of those CPPs as drug delivery systems for human disease, clinical trials have been ongoing since the middle of the 2000s (van den Berg and Dowdy, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Polyarginine (11R)-conjugated VIVIT peptide, which is a specific NFAT inhibitory peptide, was able to inhibit graft rejection of allogeneic islet transplantation in mice (Noguchi et al, 2004). More recently, TAT-CPP-conjugated RNA binding successfully delivered siRNA for efficient gene silencing in various cell types including primary T cells (Eguchi et al, 2009). Although extensive studies have suggested the possible use of those CPPs as drug delivery systems for human disease, clinical trials have been ongoing since the middle of the 2000s (van den Berg and Dowdy, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Despite various approaches have been explored, such as osmotic methods, lipid conjugation and virus vectors, most of them are limited for research and perform the best on adherent tumor cells. CPPs have demonstrated strong transfection ability by delivery siRNA into some acknowledged hard-transfected primary cells like T cells, HUVECs and hESCs 16 and even the blood-brain barrier, which indicates its potential use in vivo. 33,34 In this study, we used 3TAT-DRBD to bind sur-siRNA and delivered it to the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…To construct the A10-STD-(sur-siRNA) complex 10 mL 5 mM sur-siRNA in water was mixed with 10 mL 20-50 mM STD in PBS with 10% glycerol on ice for 30 min, then mixed with 10 mL 20 mM biotinylated A10 in PBS (pH 7.4) for another 30 min. 16 To confirm the binding between STD and sur-siRNA or A10, 10 mL sur-siRNA (diluted to 1/32 mM) and 10 mL A10 (diluted to 1/4 mM) were incubated with STD fusion protein in PBS with 10% glycerol on ice for 2 hours respectively. STD fusion protein (20 mg) was 2-folds diluted up to 1/128.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies demonstrate that protein transduction domains (PTDs), also known as cell-penetrating peptides, can deliver conjugated macromolecular cargos by penetrating the cell membrane, and they have been utilized as transport vectors in biomedical applications [5][6][7]. At present, in vivo studies of PTDs are being conducted to deliver proteins, oligonucleotides, siRNA, liposomes, and nanoparticles inside cells where they target disease-specific molecules [8][9][10][11][12]. Therefore, PTD-conjugated macromolecules are promising materials targeting intracellular molecules.…”
Section: Introductionmentioning
confidence: 99%